"Technical Note:" Optimisation of Diamond™ Nucleic Acid Dye preparation, application, and visualisation, for latent DNA detection. (January 2022) - Hughes, Deborah A.; Szkuta, Bianca; van Oorschot, Roland A.H.; Conlan, Xavier A.
Highlights: Crystal formation of Diamond Nucleic Acid Dye was observed on latent touch DNA. Spray application eliminated the formation of crystals on the substrate surface. The ethanol water ratio did not affect the fluorescence activity of the dye. The approach improved the visualisation of latent fingerprints and touch DNA. Graphical Abstract: ga1 Abstract: A targeted sampling approach of latent DNA, deposited when a person makes contact with a surface, can prove challenging during crime scene or evidence processing, with the sampling of latent DNA often relying on the expert judgement from crime scene officers and forensic examiners. As such, the ability to use the quick and robust screening tool Diamond™ Nucleic Acid Dye (DD) was explored, with a focus on the visualisation of latent DNA on non-porous substrates, namely polypropylene, acrylic, aluminium, PVC composite material, glass, and crystalline silicon. The application of DD was performed according to methods reported in literature, where 10 µL of the dye solution (20-fold dilution of DD in 75% EtOH) was applied onto a variety of non-porous substrates via a micropipette and then subsequently visualised using a portable fluorescence microscope. It was discovered that there was scope for improvement in the reported methods due to the observation of crystal formations on all test substrates upon drying of the DD, resulting in the impaired visualisation of latent DNA and fingerprint detail. Thus, changes to the EtOH water ratio of the dye solution, and changes to the mode of dye application from a micropipette to a spray application, were explored to improve the drying time of the dye and mitigate the formation of crystals. While changes to the EtOH water ratio did not improve the overall drying time, the mode of dye application enhanced visualisation, with a spray application eliminating the formation of crystals no matter the EtOH water ratio. Visualisation with a portable Dino-Lite and Zeiss Widefield fluorescence microscope were also explored, with the Zeiss Widefield fluorescence microscope proving to be useful in whole print imaging and a more efficient imaging tool in a laboratory setting.